2021
DOI: 10.1177/15579883211006003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Male Partners of Pregnant Women in the Prevention of Mother-to-Child Transmission (PMTCT) of HIV in Haiti: A Mixed-Methods Study

Abstract: This mixed-methods study aimed to determine the level of male involvement in the prevention of mother-to-child transmission (PMTCT) services in Haiti and identify barriers and associated factors. From May to June 2018, a questionnaire was used to measure the level of male involvement. Semistructured interviews with pregnant women were also conducted. Multivariate linear regression and qualitative content analyses were performed to explore factors associated and barriers to male partners’ involvement in PMTCT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The present study showed it was difficult for women to talk to their sexual partners about condom use, as demonstrated in other studies. In PNC visits, health professionals need to involve partners and provide the necessary support to pregnant women ( 32 34 ). Adequate treatment of the pregnant woman concomitantly with the treatment of the partner is a determining factor for preventing the vertical transmission of syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed it was difficult for women to talk to their sexual partners about condom use, as demonstrated in other studies. In PNC visits, health professionals need to involve partners and provide the necessary support to pregnant women ( 32 34 ). Adequate treatment of the pregnant woman concomitantly with the treatment of the partner is a determining factor for preventing the vertical transmission of syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…The study used a semi-structured individual interview guide as the primary data collection instrument. Because Haitian women often come to the prenatal clinic alone ( 29 ), the snowball method was used to recruit relatives. During prenatal clinic visits, pregnant adolescents were given a letter and a summary of the study to invite one of their relatives to participate in this research.…”
Section: Methodsmentioning
confidence: 99%